Apakah Industri Pelayaran Menjadi Pilihan yang Menarik untuk Investor? Studi Kasus PT Samudera Indonesia Tbk - Rajagukguk, Jenni Tesya Nathanya; Kuncoro, Risma Sugiarti; Setianingrum, Hanifah; Aprayuda, Riyadi (E-Jurnal Akuntansi, 2024)
Along with the economic recovery due to the pandemic, the shipping industry is strengthening again because international trade is returning to normal activities. This research aims to look at investment potential in the shipping industry with semi-strong market conditions in 2018-2023 and focuses on SMDR issuers. Purposive sampling is a technique for determining the research sample with a sample size of four companies listed on the Indonesian Stock Exchange that have the same size. The analytical tools used are Financial Ratio Analysis, Altman Z-Score, Absolute Discounted Cash Flow Valuation with the Free Cash Flow to The Firm model, Relative Comparable Companies Valuation, and Multiple Valuation and tested using Sensitivity Test and Monte Carlo Simulation. The research results show that the profitability and liquidity of shipping companies has increased in line with valuations which have a potential increase of 63.84% and a growth probability of 75%. The contribution of this research provides an overview of the shipping industry as an attractive investment option in the future. Keywords: Investment; Shipping; Efficient Market; Valuation